2022
DOI: 10.1083/jcb.202003143
|View full text |Cite
|
Sign up to set email alerts
|

Regulating peroxisome–ER contacts via the ACBD5-VAPB tether by FFAT motif phosphorylation and GSK3β

Abstract: Peroxisomes and the endoplasmic reticulum (ER) cooperate in cellular lipid metabolism. They form membrane contacts through interaction of the peroxisomal membrane protein ACBD5 (acyl-coenzyme A–binding domain protein 5) and the ER-resident protein VAPB (vesicle-associated membrane protein–associated protein B). ACBD5 binds to the major sperm protein domain of VAPB via its FFAT-like (two phenylalanines [FF] in an acidic tract) motif. However, molecular mechanisms, which regulate formation of these membrane cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 67 publications
3
49
0
Order By: Relevance
“…For example, whilst loss of PTPIP51-VAPB stimulates autophagy, increased PTPIP51-VAPB inhibits autophagy implying that dynamism in the mitochondria-ER interaction is required for this process ( Gómez-Suaga et al, 2017 )). In a similar way, whilst loss of ACBD5-VAPB tethering appears to limit peroxisomal membrane expansion, increased ACBD5 levels lead to peroxisomal elongation, potentially implying an excess membrane expansion ( Costello et al, 2017a ; Kors et al, 2022 ). Overall, this suggests that these organelle interactions involving VAP protein tethers are highly regulated.…”
Section: Vap Binding Partners and The Functions Of The Ensuing Complexmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, whilst loss of PTPIP51-VAPB stimulates autophagy, increased PTPIP51-VAPB inhibits autophagy implying that dynamism in the mitochondria-ER interaction is required for this process ( Gómez-Suaga et al, 2017 )). In a similar way, whilst loss of ACBD5-VAPB tethering appears to limit peroxisomal membrane expansion, increased ACBD5 levels lead to peroxisomal elongation, potentially implying an excess membrane expansion ( Costello et al, 2017a ; Kors et al, 2022 ). Overall, this suggests that these organelle interactions involving VAP protein tethers are highly regulated.…”
Section: Vap Binding Partners and The Functions Of The Ensuing Complexmentioning
confidence: 96%
“…Interestingly, the VAP family proteins MOSPD1 and MOSPD3 favour motifs with “two phenylalanines in a neutral tract” (FFNT) ( Cabukusta et al, 2020 ). Furthermore, the interaction with VAP can be modulated on multiple levels; for instance, the FFAT-VAP binding can be strengthened and reduced by (de)phosphorylation of the FFAT motif ( Kumagai et al, 2014 ; Johnson et al, 2018 ; Kirmiz et al, 2018 ; Di Mattia et al, 2020 ; Guillén-Samander et al, 2021 ; Kors et al, 2022 ). VAP dimerization via the TMD and coiled-coil domains might enhance the recruitment of pre-existing homodimers of FFAT proteins (e.g.…”
Section: Vap Binding Partners and The Functions Of The Ensuing Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…The model parameters (i–iii) are likely to change during cellular growth and differentiation, presumably via cellular signaling and expression levels/post-translational modifications of tethering, membrane shaping and division components. We recently demonstrated that the interaction of the peroxisomal tether ACBD5 with ER-resident VAPB is regulated by phosphorylation [ 178 ], with phosphorylation in the core region of the ACBD5 FFAT motif inhibiting interaction with the MSP domain of VAPB. Overall, we suggest that peroxisome morphology is likely to be differently affected in various cell types of patients suffering from organelle division defects.…”
Section: Modelling and Prediction Of Peroxisomal Dynamicsmentioning
confidence: 99%
“…In a recent paper published in the Journal of Cell Biology we explored regulatory mechanisms that can control peroxisome-ER interactions via phosphorylation of the tether protein ACBD5 ( Kors et al, 2022 ). Here, we summarise this work and discuss how this fits alongside other data on phosphorylation of VAP interactors to give new insights into the control of membrane contact sites involving the ER and other organelles.…”
mentioning
confidence: 99%